ESTABLSHMENT OF SOVIET POWER IN TURKESTAN. ARANGEMENTS TAKEN BY THE SOVIET AUTHORITIES IN UZBEKISTAN AND THEIR COLLONIAL ESSENNCE - Teshaboyeva Nafisa Zubaydulla qizi; Berdimurodova Dildora Qahramon qizi (TADQIQOTLAR.UZ, 2024)
Annotation: The article discusses the establishment of Soviet power in Turkestan, focusing on Uzbekistan and Turkmenistan, and analyzes the colonialist essence of Soviet actions in these regions. It examines the political, economic, cultural, and social aspects of Soviet rule, highlighting policies of control, exploitation, assimilation, and infrastructure development. Through a historical lens, it explores how Soviet authorities implemented various measures to subjugate the local populations and advance Soviet interests in the region, shaping the socio-political landscape during the Soviet era.